Investigating conditions for meaningful feedback in the context of an evidence‐based feedback programme. Issue 9 (September 2016) - Voyer, Stéphane; Cuncic, Cary; Butler, Deborah L; MacNeil, Kimberley; Watling, Christopher; Hatala, Rose
Abstract : Context: We developed, implemented and evaluated an evidence‐based programme of feedback designed to address limitations identified in the current literature. Objectives: We sought to advance understanding about how and why feedback processes might be more effective in clinical education. Methods: Three faculty members and nine first‐year internal medicine residents participated in the pilot programme. To counter challenges identified in the literature, feedback was based on direct observation, grounded in longitudinal faculty–resident relationships, and devoid of summative assessment. We used a qualitative case study design to address three research questions: (i) What benefits did the participants describe? (ii) What elements of the programme facilitated these benefits? (iii) What were the limitations and challenges of the programme? Collected data included audiotapes of interactions between faculty members and residents, field notes written during observations, and semi‐structured interviews and focus groups with resident participants. Data analysis moved cyclically and iteratively through inductive and deductive analysis. Results: Residents described benefits relating to their ways of working (clinical skills), ways of learning (accountability for learning) and ways of feeling (emotional well‐being). According to participants, specific elements of the programme that achieved these benefits included the direct observation of authentic clinical work, the longitudinal relationship with a faculty member and the emergence of feedback as a conversation between the faculty member and learner. Conclusions: We conclude that the conditions established within our pilot feedback programme influenced the learning culture for first‐year internal medicine residents by grounding direct observation in authentic clinical work and setting the observations in the context of a longitudinal, non‐assessment‐based relationship between a faculty member and resident. These conditions appeared to influence residents' participation in the feedback process, their ways of approaching their daily clinical work, their emotional well‐being and their engagement in their own learning. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss